Jackie Mason is [videorecording (DVD)] : one angry man - Moskovic, Steve; Mason, Jackie; Colby, Jamie; Darrow, Tony; Felder, Raoul; Gallagher, Mike; Levin, Mark, 1965- (SRO Entertainment, 2011)
Modeled after the stage and screen production 'Twelve Angry Men', 'One Angry Man' is a courtroom dram-edy starring Jackie Mason as himself. The characters share stories with one another about their lives and experiences, tempers flare, emotions run rampant, and Jackie realizes he may have made a wrong decision, and tries re-convincing the others. Jackie, being soft-hearted as he is, takes responsibility and tries re-convincing everyone of the plaintiff's innocence.